Comparative Study of Non Polar and Polar Solvent Extracts of Glochidion Velutinum Wight in Respect of Antioxidant and Antibacterial Action - Hossain, Md Selim; Das, Ananta Kumar; Rabbi, Fazlay; Ahmad, Mesbahuddin (Journal of Bangladesh Academy of Sciences, 2018)
Antioxidant and antimicrobial activities of non-polar and polar extracts of Glochidion velutinum Wight have been studied. The phenolic content was determined by Folin-Ciocalteu reagent and colorimetric method was used to quantify flavonoids. Antioxidant activity was also measured by DPPH free radical scavenging assay and disk diffusion method was applied to test antimicrobial activity. Of the hexane, chloroform, ethanol and methanol extracts of Glochidion velutinum, higher total phenolic and flavonoid contents were found in methanol and ethanol extracts. Moreover, ethanol and methanol extracts also showed better antimicrobial and antioxidant activities than the other two extracts. The presence of various phytochemicals e.g. alkaloids, tannins, phenols etc in these extracts also substantiated the observed antioxidant and antimicrobial activities. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 247-252, 2017